2021
DOI: 10.3390/foods10112872
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Gourd Honey Ameliorates Hepatic and Renal Diabetic Complications on Type 2 Diabetes Rat Models by Antioxidant, Anti-Inflammatory, and Anti-Apoptotic Mechanisms

Abstract: Honey has several pharmacological effects, including anti-diabetic activity. However, the effectiveness of bitter gourd honey (BGH) in the treatment of diabetes mellitus (DM) is unknown. The aim of this study was to determine the antioxidant, anti-inflammatory, and anti-apoptotic properties of BGH on the kidney and liver of a streptozotocin-induced diabetes rat model. Methods: A single dose (nicotinamide 110 mg/kg, streptozotocin (STZ) 55 mg/kg, intraperitoneal (i.p.)) was used to induce DM in male rats. For 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior research that found flavonoids to have hepatorenal protective properties [ 29 ]. Rosinidin molecules significantly suppress amylase enzymes, signifying anti-diabetic effects; this is consistent with prior studies on other flavonoids [ 30 , 31 , 32 ]. Furthermore, rosinidin protects vital tissues including the pancreas, thereby lowering risks of diabetes-related complications.…”
Section: Discussionsupporting
confidence: 91%
“…Usually, in rats or mice, a single dose in the range of 50 to 65 mg/kg is used most frequently (Goyal et al 2016 ; Wang-Fischer and Garyantes 2018 ). Also in some studies, a single dose of nicotinamide (110 mg/kg) along with STZ (55 mg/kg) was used to induce DM in rats (Arigela et al 2021 ), while the administration of a low dose (40 mg/kg) of STZ along with a high-fat diet can develop a metabolic syndrome model (Suman et al 2016 ; Ameer and Salman 2021 ). GLUT-2 is a plasma membrane glucose transporter through which STZ enters and accumulates in pancreatic β-cell (Tjälve et al 1976 ; Damasceno et al 2014 ).…”
Section: Stz-induced Diabetesmentioning
confidence: 99%
“…The study was approved by ethical committee, institutional animal ethics committee, Faculty of Medicine, Universiti Malaya, Kuala Lumpur, Malaysia (2019-210806/PHYSIO/R/GN). The induction of diabetics was described previously [ 16 ]. Briefly, overnight fasting rats were injected with nicotinamide (110 mg/kg bw; i.p) after 15 min, rats were injected with streptozotocin (STZ) at 55 mg/kg bw.…”
Section: Methodsmentioning
confidence: 99%